One Novel Phantom-Less Quantitative Computed Tomography System for Auto-Diagnosis of Osteoporosis Utilizes Low-Dose Chest Computed Tomography Obtained for COVID-19 Screening - Xiongfeng, Tang; Cheng, Zhang; Meng, He; Chi, Ma; Deming, Guo; Huan, Qi; Bo, Chen; Kedi, Yang; Xianyue, Shen; Tak-Man, Wong; William Weijia, Lu; Yanguo, Qin (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The diagnosis of osteoporosis is still one of the most critical topics for orthopedic surgeons worldwide. One research direction is to use existing clinical imaging data for accurate measurements of bone mineral density(BMD) without additional radiation. Methods: A novel phantom-less quantitative computed tomography(PL-QCT) system was developed to measure BMD and diagnose osteoporosis, as our previous study reported. Compared with traditional phantom-less QCT, this tool can conduct an automatic selection of body tissues and complete the BMD calibration with high efficacy and precision. The function has great advantages in big data screening and thus expands the scope of use of this novel PL-QCT. In this study, we utilize lung cancer, or COVID-19 screening Low-dose computed tomography (LDCT) of 649 patients for BMD calibration by the novel PL-QCT, and we made the BMD changes with age based on this PL-QCT. Results: The results show that the novel PL-QCT can predict osteoporosis with relatively high accuracy and precision using the LDCT and the AUC values range from 0.68 to 0.88 with DXA results as diagnosis reference. The relationship between PL-QCT BMD with age is close to the real trend population (from ~160mg/cc in less than 30 years old to ~70 mg/cc in larger than 80years old for both female and male groups). Additionally, the calculation results of Pearson’s r values for correlation between CT values with BMD in different CT devices were 0.85-0.99. Conclusion: To our knowledge, it is the first time for automatic PL-QCT to evaluate the performance against dual-energy X-ray absorptiometry (DXA) in LDCT images. The results indicate that it may be a promising tool for individuals screened for Low-dose chest computed tomography.